A 'place-based' approach to work and employment: The end of reciprocity for ordinary working families and 'giggers' in a place. (May 2022) - Clark, Ian; Lawton, Chris; Stevenson, Clifford; Vickers, Tom; Dahill, David
The authors define 'place basing' as the study of work and employment in a particular place. They are interested in understanding the limitations of work opportunities therein and so focus on workers and jobs that are not subject to the threat of off-shoring or relocation elsewhere but which are low paid and insecure. The authors theorize three contributions to new knowledge that flow from a place-based study of work and employment by demonstrating how precarious flexible often zero hour work eschews reciprocity between employer and employees and workers. They focus their research on ordinary working families and the 'permissive visibility' of bad work. The research points to an idealized model of individual and family economic functioning that is able to cope with physical and mental challenges individually without burdening the state. As the findings on workers and households demonstrate, this ideal is far from the reality they experience.